Being a pilgrim art and ritual on the medieval routes to Santiago - Ashley, Kathleen M. 1944-; Deegan, Marilyn (Lund Humphries, 2009)
The Way of St. James has been a pilgrimage event for over 1000 years as people have flocked to the site of the burial of the apostle St. James the Great. This book captures the experience of the medieval pilgrim through an examination of art, historical and social contexts as well as themes related to pilgrimage such as music, legend and ritual.